Factors that Affect the Economic Participation of Female Labor with Married Status in Central Java (Analysis of Sakernas Data 2017) - Caroline, K (KnE Social Sciences, 2018)
Central Java is one of the provinces in Java Island with the lowest economic growth rate and has the third rank for the number of female labor with married status from six provinces in Java Island in 2017. Therefore this study aims to analyse the factors which affect the economic participation of female labor with married status in Central Java using Sakernas data of August 2017. The result of analysis by binary logistic regression method shows that the variable of residence (rural), age, and education have a significant positive effect on the economic participation of female labor with married status (as labor force) while the number of toddlers and the existence of toddlers have a significant negative effect on the economic participation of female labor with married status (as labor force). Therefore, efforts are needed from all parties, especially the government as policy maker with availability of daycare center, equal employment opportunities without being limited by age, and giving motivation to women for getting higher education to increase economic growth rate in Central Java by utilizing the availability of labor especially women with married status. Keywords: economic growth, female labor, logistic regression, labor force